Эколого-морфологическая характеристика свиньи дикой Беловежской пущи - Козло, П.Г. (Вестник зоологии, 1968)
212 Sus scrofa, obtained in spring-summer season of 1960-1965, were studied. On the basis of tooth appearance, change and degree of their obliteration eight age groups are distinguished. Comparative ecological and morphological study of the main morphometric characters showed that the peculiarities of Sus scrofa body frame and functions of the separate parts and organs are determined by the hereditary grounds and the specificity of this species ecology. The development indices of heart, lungs, liver, kidneys, spleen and the relative length of bowels depend on the body dimensions, metabolism and general activity of animals. The differences in the manner of life and behaviour of Sus scrofa considerably affect the functional loading of organs, which conditions their relative dimensions and weight.